Sie sind auf Seite 1von 7

Solutions for Math 311 Assignment #10

(1) By differentiating the Taylor series representation

X
1
=
z n (|z| < 1)
1z
n=0
obtain the expansions

X
1
=
(n + 1)z n (|z| < 1)
2
(1 z)
n=0
and

X (n + 1)(n + 2)
1
z n (|z| < 1).
=
(1 z)3
2
n=0
Solution. We have

0 X

1
1
=
(z n )0
=
2
(1 z)
1z
n=0
=

nz

n1

nz

n1

(n + 1)z n

n=0

n=1

n=0

and
1
1
=
(1 z)3
2

1
(1 z)2

0
=

1X
((n + 1)z n )0
2 n=0

1X
1X
(n + 1)nz n1 =
(n + 1)nz n1
=
2 n=0
2 n=1
=

X
(n + 2)(n + 1)
n=0

zn

for |z| < 1.


(2) By substituting 1/(1 z) for z in the expansion

X
1
=
(n + 1)z n (|z| < 1)
2
(1 z)
n=0
derive the Laurent series representation

X
(1)n (n 1)
1
=
(1 < |z 1| < ).
n
z2
(z

1)
n=2
1

Solution. When 1 < |z 1| < , |(1 z)1 | < 1 and hence


1
1
1
1
=
=
2
2
2
z
((1 z) 1)
(1 z) (1 (1 z)1 )2

X
X
n+1
1
n
(n + 1)(1 z) =
=
2
(1 z) n=0
(1 z)n+2
n=0

X
X
n1
(1)n (n 1)
=
=
(1 z)n
(z 1)n
n=2
n=2

(3) Find the Taylor series expansions of cos z at z = /2. Use


this to prove that if

cos z

when z 6= /2,
2
f (z) = z (/2)2
1
when z = /2,

then f (z) is an entire function.


Proof. At z = /2,
cos(z) = cos(z /2 + /2) = sin(z /2)

X
(1)n 
2n+1
=
z
(2n + 1)!
2
n=0

X
(1)n+1 
2n+1
=
z
(2n + 1)!
2
n=0
for |z /2| < . At z = /2,
cos(z) = cos(z + /2 /2) = sin(z + /2)

X
(1)n 
2n+1
z+
=
(2n + 1)!
2
n=0
for |z + /2| < . To show that f (z) is entire, we need to show
that f (z) is analytic everywhere. Since f (z) = cos z/(z 2
(/2)2 ) is analytic at all z 6= /2, it suffices to prove that
f (z) is analytic at z = /2.
Consider the power series

X
(1)n+1 
2n
g(z) =
z
.
(2n
+
1)!
2
n=0

Since

X
(1)n+1 
2n+1
z
(2n + 1)!
2
n=0

converges for |z /2| < ,

X
2n
(1)n+1 
z
(2n + 1)!
2
n=0

converges for |z /2| < . Therefore, g(z) is analytic at


/2. Hence g(z)/(z + /2) is analytic at /2. Notice that
g(z) = cos z/(z /2) for z 6= /2 by the Taylor series of
cos z/(z /2). Therefore, g(z)/(z +/2) = f (z) for z 6= /2.
And since g(/2) = 1, g(/2)/(/2 + /2) = 1/ and hence
g(z)/(z + /2) = f (z) for all z 6= /2. Therefore, f (z) is
analytic at /2. Similarly, we can show that f (z) is analytic at
/2. So f (z) is entire.

(4) Prove that if f is analytic at z0 and f (z0 ) = f 0 (z0 ) = ... =
f (m) (z0 ) = 0, then the function g defined by means of the equations

f (z)

when z 6= z0 ,

(z z0 )m+1
g(z) =
f (m+1) (z0 )

when z = z0

(m + 1)!
is analytic at z0 .
Proof. Since f (z) is analytic at z0 , f (z) is analytic in |zz0 | < r
for some r > 0. Therefore,
f (z) =

X
f (n) (z0 )
n=0

n!

(z z0 )n

for |z z0 | < r. And since f (z0 ) = f 0 (z0 ) = ... = f (m) (z0 ) = 0,


f (z) =

X
X f (n) (z0 )
f (n) (z0 )
(zz0 )n = (zz0 )m+1
(zz0 )nm1
n!
n!
n=m+1
n=m+1

for |z z0 | < r. Consider the power series


h(z) =

X f (n) (z0 )
(z z0 )nm1
n!
n=m+1

It converges for |z z0 | < r. Therefore, h(z) is analytic in


|z z0 | < r. Since
( f (z)
when z 6= z0
m+1
0)
h(z) = (zz
f (m+1) (z0 )
when z = z0
(m+1)!
g(z) = h(z) for all |z z0 | < r. So g(z) is analytic at z0 .
(5) Use multiplication of series show that
ez
1
1
5 2
=
+
1

z + ...
z(z 2 + 1)
z
2
6
for 0 < |z| < 1.
Solution. Since
z

e =

X
zk
k=0

k!

for |z| < and

X
X
1
1
2 l
(1)l z 2l
(z
)
=
=
=
z2 + 1
1 (z 2 )
l=0
l=0
for |z| < 1, we have
ez
1
=
2
z(z + 1)
z
=

X
zk
k=0

k!

!
(1)l z 2l

l=0

an z n

n=

for 0 < |z| < 1, where


X (1)l
=
an =
k!
k+2l1=n
k,l0

X
0l(n+1)/2

(1)l
.
(n + 1 2l)!

So an = 0 for n < 1,
(1)0
(1)0
(1)0 (1)1
1
a1 =
= 1, a0 =
= 1, a1 =
+
=
0!
1!
2!
0!
2
and
(1)0 (1)1
5
a2 =
+
= .
3!
1!
6
Therefore,

ez
1
1
5 2 X
= +1 z z +
an z n
z(z 2 + 1)
z
2
6
n=3

for 0 < |z| < 1.


(6) Use division to obtain the Laurent series representation
1
1 1
1
1 3
= + z
z + ...
z
e 1
z 2 12
720
for 0 < |z| < 2.
Solution. Since
z

e 1=

X
zn

n!

n=0

=z

n=1

=z

1=

X
zn
n=1

z n1
=z
n!

1+

X
n=1

n!

1+

zn
(n + 1)!

X
z n1
n=2

n!

we have
1
1
=
z
e 1
z

1+

X
n=1

zn
(n + 1)!

!1

!k

n
X
1X
z
=
(1)k
z k=0
(n + 1)!
n=1



2
1 1 z
z2 z3 z4
1 z
z2 z3
=
+
+
+
+ ... +
+
+
+ ...
z z 2! 3!
4!
5!
z 2! 3!
4!
3

4
1z
z2
1 z
+
+ ... +
+ ... + ...

z 2! 3!
z 2!




1
1
1
2
1
1
1
= + +
z+ +

z2
z 2!
3! (2!)2
4! (2!)(3!) (2!)3



X
2
1
3
1
1
3
+ +
+

+
z +
an z n
5! (2!)(4!) (3!)2 (2!)2 (3!) (2!)4
n=4

1 1
1
1 3 X
= + z
z +
an z n .
z 2 12
720
n=4

Since 1/(ez 1) is analytic in {z : ez 1 6= 0} = {z 6= 2ni :


n integers}, it is hence analytic in 0 < |z| < 2. Therefore, the
above Laurent series converges in 0 < |z| < 2.
(7) Find the residue at z = 0 of the function

1
;
2
z + z

1
;
(b) z cos
z
sinh z
.
(c) 4
z (1 z 2 )
Solution. (a) Since
(a)

1
1X
1 1
=
(z)n
=
z + z2
z1+z
z n=0

1 X (1)n
= +
,
z n=1 z n1
Resz=0 1/(z + z 2 ) = 1.
(b) Since
 

X
(1)n
1
=z
z cos
z
(2n)!z 2n
n=0
=

X
n=0

(1)n
(2n)!z 2n1

X (1)n
1
=z
+
,
2z n=2 (2n)!z 2n1
Resz=0 z cos(1/z) = 1/2.
(c) Since
sinh z
ez ez
1
=
= 4
4
2
4
2
z (1 z )
2z (1 z )
2z
1
2z 4

1
z3

1
z3
we obtain

zn
(1)n

n! n=0
n!
n=0
!
!
X
z 2n

2z 2n+1
(2n + 1)!
n=0
n=0
!
!

2n
X
X
z
z 2n
(2n
+
1)!
n=0
n=0



z2
1+
+ ... 1 + z 2 + ...
6

X
zn

Resz=0

sinh z
1
7
=
1
+
=
z 4 (1 z 2 )
6
6

!
X
n=0

z 2n

(8) Evaluate the integral of each of these functions around the circle
|z| = 3 oriented counterclockwise:
exp(z)
(a)
;
z2
z+1
.
(b) 2
z 2z
Solution. (a) By Cauchy Integral Theorem,
Z
Z
exp(z)
exp(z)
exp(z)
dz
=
dz
=
2i
Res
.
z=0
z2
z2
z2
|z|=3
|z|=r
And since

exp(z)
1 X (z)n X (1)n z n2
=
= 2
z2
z n=0 n!
n!
n=0
Resz=0 exp(z)/z 2 = 1 and hence
Z
exp(z)
dz = 2i.
z2
|z|=3
(b) By Cauchy Integral Theorem,
Z
Z
z+1
z+1
z+1
dz =
+
2
2
2
|z|=3 z 2z
|z|=r z 2z
|z2|=r z 2z
z+1
z+1
= 2i Resz=0 2
+ 2i Resz=2 2
.
z 2z
z 2z
And since
1
3
z+1
=

+
z 2 2z
2z 2(z 2)


z+1
3
1
Resz=0 2
= Resz=0
+ Resz=0
z 2z
2z
2(z 2)


1
1
= Resz=0
=
2z
2
and


z+1
1
3
Resz=2 2
= Resz=2
+ Resz=2
z 2z
2z
2(z 2)


3
3
= Resz=2
= .
2(z 2)
2
Therefore,


Z
z+1
3 1
dz = 2i

= 2i.
2
2 2
|z|=3 z 2z